AN ANALYTICAL STUDY OF IMPORTS IN ALGERIA DURING THE PERIOD (1992-2012) - Imen, Kerroucha; Belkacem, Zairi (European Scientific Journal, ESJ, 2014)
This study showed a number of previous studies which focused on the demand for imports of many countries, whether developed or developing countries and in varying degrees of economic growth; where the aim of these studies search for variables and factors that determine the overall demand for imports. The majority of the studies concluded that income and relative prices are considered key factors in the interpretation and determine the level of aggregate demand for imports. The study aimed to identify the factors that affect the composition of each commodity and geographical distribution of imports in Algeria; and have been used in order to achieve this some standards for concentration commodity and geographical location, and the relative importance from the period from 1992 to 2012.